The Construction of Identities: Power Relations in Naomi Wallace’s In the Heart of America - Aqeeli, Ammar Abduh (Journal of Literary Studies)
This article explores how Naomi Wallace’s In the Heart of America demonstrates the interconnectedness of xenophobia, racism and other forms of discrimination in American life and politics. Through the critiques offered by Louis Althusser, Michel Foucault and Judith Butler, this article investigates the relationships between ideological state apparatuses, production of power and the construction of social identities. The subjugated characters in the play attempt to resist, negotiate and accommodate normative or regulative discursive processes that impose fixed identities upon them. Wallace’s play demonstrates that resistance constitutes power, which can be either weak, submissive, creative, and/or productive. Raising awareness of the possibilities of resistance to subjectifying power is what In the Heart of America yearns to do.